PERSIAPAN TOTAL QUALITY MANAGEMENT (TQM) - FITRIANI Fitriani (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract: School is the main place in improving the quality and initial preparation to face the competition that exists today, namely by creating good and quality school management in accordance with the demands of TQM, because school management is a place to create quality and excellence. School management will be carried out if supported by human resources (HR) who have the ability, integration and high will. This is where the application of TQM that prioritizes quality reliability can be applied in the world of education to produce the best quality education in the school environment.